Durability of Adult Plant Resistance Gene Yr18 in Partial Resistance Behavior of Wheat (Triticum aestivum) Genotypes with Different Degrees of Tolerance to Stripe Rust Disease, Caused by Puccinia striiformis f. sp. tritici: A Five-Year Study - Ghady E. Omar (MDPI AG, 2021)
Adult plant resistance in wheat is an achievement of the breeding objective because of its durability in comparison with race-specific resistance. Partial resistance to wheat stripe rust disease was evaluated under greenhouse and field conditions during the period from 2016 to 2021. Misr 3, Sakha 95, and Giza 171 were the highest effective wheat genotypes against Puccinia striiformis f. sp. tritici races. Under greenhouse genotypes, Sakha 94, Giza 168, and Shandaweel1 were moderately susceptible, had the longest latent period and lowest values of the length of stripes and infection frequency at the adult stage. Partial resistance levels under field conditions were assessed, genotypes Sakha 94, Giza 168, and Shandaweel1 exhibited partial resistance against the disease. Leaf tip necrosis (LTN) was noted positively in three genotypes Sakha 94, Sakha 95, and Shandaweel1. Molecular analyses of Yr18 were performed for csLV34, cssfr1, and cssfr2 markers. Only Sakha 94 and Shandaweel1 proved to carry the Yr18 resistance allele at both phenotypic and genotypic levels. Scanning electron microscopy (SEM) observed that the susceptible genotypes were colonized extensively on leaves, but on the slow-rusting genotype, the pustules were much less in number, diminutive, and poorly sporulation, which is similar to the pustule of NIL Jupateco73 ‘R’.